Taking a Back Seat: Synaptic Vesicle Clustering in Presynaptic Terminals - Pechstein, Arndt; Shupliakov, Oleg (Frontiers in Synaptic Neuroscience, 2010)
Central inter-neuronal synapses employ various molecular mechanisms to sustain neurotransmitter release during phases of high-frequency synaptic activity. One of the features ensuring this property is the presence of a pool of synaptic vesicles (SVs) in the presynaptic terminal. At rest and low rates of stimulation, most of the vesicles composing this pool remain in a tight cluster. They are actively utilized when neurons fire action potentials at higher rates and the capability of the recycling machinery is limited. In addition, SV clusters are capable of migrating between release sites and reassemble into clusters at neighboring active zones (AZs). Within the cluster, thin “tethers” interconnect SVs. These dynamic filamentous structures are reorganized during stimulation thereby releasing SVs from the cluster. So far, one protein family, the synapsins, which bind actin filaments and vesicles in a phosphorylation-dependent manner, has been implicated in SV clustering in vertebrate synapses. As evident from recent studies, many endocytic proteins reside in the SV cluster in addition to synapsin. Here we discuss alternative possible mechanisms involved in the organization of this population of SVs. We propose a model in which synapsins together with other synaptic proteins, a large proportion of which is involved in SV recycling, form a dynamic proteinaceous “matrix” which limits the mobility of SVs. Actin filaments, however, do not seem to contribute to SV crosslinking within the SV cluster, but instead they are present peripherally to it, at sites of neurotransmitter release, and at sites of SV recycling.